The Brokenwood mysteries. Series 4 [videorecording (DVD)] - Rea, Neill, 1971-; Sutherland, Fern; Sampson, Nic, 1986- (Acorn, 2018)
Detective Senior Sergeant Mike Shepherd, Detective Kristin Sims and DC Sam Breen continue to work on solving crimes in the New Zealand town of Brokenwood.